2019
DOI: 10.1016/j.bone.2018.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic dynamic during endochondral ossification and articular cartilage development

Abstract: Within the last decade epigenetics has emerged as fundamental regulator of numerous cellular processes, including those orchestrating embryonic and fetal development. As such, epigenetic factors play especially crucial roles in endochondral ossification, the process by which bone tissue is created, as well during articular cartilage formation. In this review, we summarize the recent discoveries that characterize how DNA methylation, histone posttranslational modifications and non-coding RNA (e.g., miRNA and lc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 116 publications
5
22
0
Order By: Relevance
“…Indeed, consistent with the proposed influence of hypomethylation on the activation of prochondrogenic genes (see review by ref. 22 ), the addition of 5-azacytidine to micromass cultures promoted chondrogenesis at levels similar to what was observed after Dnmt3b gene silencing ( Fig. 7j-l).…”
Section: Resultssupporting
confidence: 78%
“…Indeed, consistent with the proposed influence of hypomethylation on the activation of prochondrogenic genes (see review by ref. 22 ), the addition of 5-azacytidine to micromass cultures promoted chondrogenesis at levels similar to what was observed after Dnmt3b gene silencing ( Fig. 7j-l).…”
Section: Resultssupporting
confidence: 78%
“…(13) Osteoblasts (ostb) play a central role in both intramembranous ossification and in the more widespread and complicated endochondral ossification pathway for bone formation based upon chondrocytes (chond). (11) Surprisingly, there is evidence for hypertrophic chond transdifferentiating to ostb, which is consistent with the considerable overlap of transcription profiles of these two morphologically dissimilar bone cell types. (14,15) Ostb and chond are derived from a heterogeneous mixture of bone-derived stem or stem-like cells commonly referred to as mesenchymal stem cells (MSC).…”
Section: Introductionsupporting
confidence: 67%
“…All but SPECC1 have known bone-related functions. (11,18,(27)(28)(29)(30) Because we recently analyzed EnhPro SNPs for TBX15, (18) we eliminated it as well as SPECC1 from further consideration. Alternatively, we identified seven additional EnhPro SNP-associated genes, HMGA2, BMP5, DLX6, SIX1, SMAD3, TRPS1, and WNT7B, that were strongly enriched in bone biology-related Gene Ontology (GO) terms, had literature references for their skeletal association, and displayed appreciable expression in ostb, chond, or MSC (Supplemental Table S5).…”
Section: Prioritization Of 16 Snps As Candidate Causal Regulatory Snpmentioning
confidence: 99%
See 1 more Smart Citation
“…Histone acetylation and deacetylation regulate many steps of myogenesis [47]. Histone deacetylases (HDAC) contribute to the molecular pathways and chromatin changes that regulate the tissue-specific gene expression during chondrocyte and osteoblast specification [48]. In this study, we demonstrated a morphological correlation between the muscles and bones during E15 and P0.…”
Section: Discussionmentioning
confidence: 58%